1995
DOI: 10.1002/hep.1840220425
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic mast cells in chronic liver diseases

Abstract: Mast cells are known to be present in human liver but their distribution and density in normal livers and in chronic liver diseases have not previously been examined. In this study, we quantified mast cell numbers and examined their distribution in percutaneous biopsy specimens from normal livers (n = 8) and in two chronic progressive liver diseases: primary biliary cirrhosis (PBC) (n = 40) and alcoholic liver disease (n = 33). We compared differences in mast cell density between these two forms of chronic liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
3
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 14 publications
6
97
3
3
Order By: Relevance
“…[48][49][50] Our present study focused primarily on the paracrine influence induced by mast cells on cholangiocytes; however, in data not shown here, we found that the proliferative response of hepatocytes was decreased in BDL þ cromolyn sodium-treated rats compared with BDL alone, and HSC activation is diminished after BDL þ cromolyn sodium treatment, suggesting that mast cell stabilization can also influence other liver cell types in vivo.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…[48][49][50] Our present study focused primarily on the paracrine influence induced by mast cells on cholangiocytes; however, in data not shown here, we found that the proliferative response of hepatocytes was decreased in BDL þ cromolyn sodium-treated rats compared with BDL alone, and HSC activation is diminished after BDL þ cromolyn sodium treatment, suggesting that mast cell stabilization can also influence other liver cell types in vivo.…”
Section: Discussionmentioning
confidence: 57%
“…Histological analysis has demonstrated that mast cells are present in cirrhosis, fibrosis, hepatitis and cholangiopathies. 18,49,50 Mast cells are found in various areas of the liver depending upon the etiology. For example, and in support of our current findings, in both PSC and PBC, mast cells are found surrounding damaged bile ducts, portal triads and portal tracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[47][48][49] Indeed, some of those mediators like nitric oxide and cytokines have been shown to affect cholangiocyte biology. 50 Furthermore, in chronic liver diseases including PBC there is increased number of mast cells, 51 which causes a Figure 5 Measurement of the number of CK-19-positive cholangiocytes in liver sections from rats (that immediately after BDL) were treated with NaCl, RAMH, thioperamide maleate (H3R antagonist) or histamine in the absence or presence of thioperamide maleate for 1 week. In BDL rats, chronic RAMH administration induced a decrease in the number of CK-19-positive (see arrows) cholangiocytes compared to NaCl-treated rats.…”
Section: Discussionmentioning
confidence: 99%
“…51 Moreover, histamine serum levels are increased in patients with chronic cholestatic liver diseases. 52 Our findings are relevant to these cholangiopathies, as we have demonstrated that histamine, increased histamine serum levels and activation of H3R modulate the proliferative response of cholangiocytes to cholestasis.…”
Section: Histamine Regulation Of Cholangiocyte Growthmentioning
confidence: 99%